(untitled) (MIST International Journal of Science and Technology, 2025)
Bangladesh’s shipbuilding sector makes a significant contribution to the country’s economy. However, it is also associated with occupational risks for its workforce. This paper aims to review and explore existing literature on assessing and managing these risks within the context of Bangladesh shipbuilding industry. The review delved into different types of hazards encountered by shipyard workers, including physical, chemical, and biological dangers, by analyzing incident reports, safety audits, and exposure data elaborated in the literature. Furthermore, the review also examines established methods applied to the international and local shipbuilding industry for risk assessment and management and makes a comparison to find the gap in the literature. The study reveals a significant amount of literature covering various focus areas within the global shipbuilding sector. However, only a limited number of these works are relevant to Bangladesh shipbuilding industry, and among them, only very few papers deal with the Occupational Health and Safety assessment technique. This highlights a huge gap in the literature and suggests a need for more studies regarding Occupational Health and Safety management in Bangladesh shipbuilding. MIJST, Vol. 13, June 2025 : 37-47 DOI: https://doi.org/10.47981/j.mijst.13(01)2025.483(37-47)